Analisis Laporan Realisasi Anggaran Bidang Bina Marga pada Kantor Dinas Pekerjaan Umum dan Perumahan Rakyat Provinsi Jambi - Raudho Lestari; Moh. Ihsan; Dessy Elliyana (Pajak dan Manajemen Keuangan, 2025)
This study, entitled Analysis of Budget Realization Report in the Road and Bridge Division of the Public Works and Housing Office of Jambi Province, aims to analyze the Budget Realization Report (LRA) and assess the effectiveness and efficiency of budget utilization during the 2021–2023 period. The research employs a quantitative method with a descriptive approach. Data were collected through interviews, financial report documentation, and observation, using purposive sampling techniques. The findings indicate that revenue realization was categorized as effective, with achievement ratios of 96.90% in 2021, 96.70% in 2022, and 96.24% in 2023. Meanwhile, expenditure realization was classified as highly efficient, with ratios of 17.91% in 2021, 11.67% in 2022, and 16.87% in 2023. Based on these results, it can be concluded that the budget management of the Road and Bridge Division at the Public Works and Housing Office of Jambi Province was both effective and highly efficient throughout the study period, and it may serve as a valuable reference for improving infrastructure budget management at the regional level.